The structure and function of hyaluronan-binding proteins in extracellular matrix assembly - Seyfried, N (2004)
﻿ The chondroitin sulfate proteoglycan (CSPG) aggrecan forms link protein-stabilised complexes with hyaluronan (HA), via its N-terminal G1-domain, that provide cartilage with its load bearing properties. Similar aggregates (potentially containing new members of the link protein family), in which other CSPGs (i.e., versican, brevican and neurocan) substitute for aggrecan, may contribute to the structural integrity of many other tissues including skin and brain. In this thesis, cartilage link protein (cLP) and the G1-domains of aggrecan (AG1) and versican (VG1) were expressed in Drosophila S2 cells, purified to homogeneity and functionally characterised. The recombinant human proteins were found to have properties similar to those described for the native molecules. For example cLP formed dimers, and HA decasaccharides (HA 10-mers) were the minimum size that could compete effectively for their binding to polymeric HA. In addition, gel filtration and protein cross-linking/MALDI-TOF peptide fingerprinting showed that cLP and AG1 interact in the absence or presence of HA. Conversely, cLP and VG1 did not bind directly to each other hi solution yet formed ternary complexes with HA24. N-linked glycosylation of VG1 and AG1 was demonstrated to be unnecessary for either HA binding or the formation of ternary complexes. Additionally, the length of HA required to accommodate two G1-domains was found to be significantly larger for aggrecan than versican, which may reflect differences hi the conformation of HA stabilised on binding these proteins. To further investigate protein-HA interactions, fluorescent HA oligosaccharides were prepared and characterised. HA oligosaccharides labelled with the fluorophore 2-aminobenzoic acid (2AA) from four to 40 residues hi length were purified to homogeneity by ion exchange chromatography using a logarithmic gradient. Molecular weight and purity characterisation of HA oligosaccharides was facilitated by 2AA derivitisation since it enhanced signals in MALDI-TOF mass spectrometry and improves fluorophore-assisted carbohydrate electrophoresis (FACE) analysis by avoiding the inverted parabolic migration characteristic of 2-aminoacridone (AMAC) labelled sugars. The small size and shape of the fluorophore maintains the biological activity of the derivatised oligosaccharides, as demonstrated by their ability to compete for polymeric hyaluronan binding to VG1, AG1 and cLP. An electrophoretic mobility shift assay was used to study VG1 binding to 2AA-labelled HA 8-, 10-, 20-, 30- and 40-mers and although no stable VG1 binding was observed to labelled 8-mers, the equilibrium dissociation constant (100 nM) for VG1 with HA 10-mers was estimated from densitometry analysis of the free oligosaccharide. Interactions involving 2AA labelled HA 20-, 30-, and 40-mers with VG1 also displayed positive cooperativity. Therefore, oligosaccharides labelled with 2-aminobenzoic acid are biologically active and show excellent potential as probes in fluorescence-based assays that investigate protein-carbohydrate interactions.